Targeting Tunable Physical Properties of Materials for Chronic Wound Care - Wang, Yuzhen; Armato, Ubaldo; Wu, Jun (Frontiers in Bioengineering and Biotechnology, 2020)
Chronic wounds caused by infections, diabetes, and radiation exposures are becoming a worldwide growing medical burden. Recent progress highlighted the physical signals determining stem cell fates and bacterial resistance, which holds potential to achieve a better wound regeneration in situ. Nanoparticles (NPs) would benefit chronic wound healing. However, the cytotoxicity of the silver NPs (AgNPs) has aroused many concerns. This review targets the tunable physical properties (i.e., mechanical-, structural- and size-related properties) of either dermal matrixes or wound dressings for chronic wound care. Firstly, we discuss the recent discoveries about the mechanical- and structural-related regulation of stem cells. Specially, we point out the currently undocumented influence of tunable mechanical and structural properties on either the fate of each cell type or the whole wound healing process. Secondly, we highlight novel dermal matrixes based on either natural tropoelastin or synthetic elastin-like recombinamers (ELRs) for providing elastic recoil and resilience to the wounded dermis. Thirdly, we discuss the application of wound dressings in terms of size-related properties (i.e. metal NPs, lipid NPs, polymeric NPs). Moreover, we highlight the cytotoxicity of AgNPs and propose the size-, dose- and time-dependent solutions for reducing their cytotoxicity in wound care. This review will hopefully inspire the advanced design strategies of either dermal matrixes or wound dressings and their potential therapeutic benefits for chronic wounds.